Fitness Profiling in Women Soccer: Performance Characteristics of Elite Turkish Women Soccer Players - Aras Beka Yaşar; Serdar Bayrakdaroğlu; Beyza Yıldız; İbrahim Can (Selcuk University, 2019)
The aim of this investigation was to evaluate an overall performance of the elite women football players. In accordance with this purpose, 11 women football players (age: 21,5 ± 2,58 years; height: 160,8 ± 5,17 cm; weight: 55,8 ± 7,23 kg) who plays in Turkish Women's 1st Football League participated voluntarily. In order to measure athlete's aerobic capacity, Yo-Yo intermittent recovery test (Yo-Yo IR1) was applied and maximal oxygen uptake (VO2max) values were estimated by using running distances obtained from the test results. The Wingate anaerobic power test (WanT) to measure the athlete's anaerobic properties, the vertical jump (VJ) and standing long jump (SLJ) tests to determine explosive power, the Illinois agility test to measure agility skills, 10 and 30 meters sprint runs to measure sprint performances, hand grip and back-leg strength tests to measure strength characteristics were used. In order to obtain power and velocity parameters, loaded-squat jump (SJLoaded) was applied with an resistance that equaled to 40% of body weight and bench throw (BT) was applied with an resistance that equaled to 30% of body weight of the participants by applying an isoinertial device and results of peak power (PP), peak velocity (PV), mean propulsive power (MPP), and mean propulsive velocity (MPV) during both movements were recorded. Statistical analysis was used in the assessment of the data. According to analysis results, it was achieved that Yo-Yo IR1 running distances was as 676,3 ± 156,4 meters, while VO2max values of athletes were estimated as 42,2 ± 1,20 ml/kg-1/min-1. Relative and absolute anaerobic power values for elite women football players were obtained as 439,7 (± 61,18 W) and 8,04 (± 1,09 W/kg) for maximal anaerobic power, 316,1 (± 34,46 W) and 5,78 (± 0,56 W/kg) for maximal anaerobic capacity, 193,6 (±22,30 W) and 3,55 (± 0,61 W/kg) for minimal anaerobic power, respectively. In addition, fatigue index values measured as 55,7 (± 3,75 %). Participant's right and left hand grip strength values were obtained as 30,6 (± 4,62 kg) and 29,6 (± 4,5 kg), back and leg strength values measured as 90,2 (± 18,7 kg) and 101,8 (± 29,5 kg), respectively. Participant's 10 and 30 meters sprint duration were obtained as 1,85 (± 0,12 sec) and 4,96 (± 0,34 sec). SLJ, VJ and agility values were obtained as 178,4 (± 21,1 cm), 35,7 (± 4,60 cm) and 17,6 (±0,67 sec), respectively. Velocity and power values for athletes during BT movement were obtained as 1,21 (± 0,10 m/sec) for MPV, 2,04 (± 0,18 m/sec) for PV, 353,6 (± 83,2 W) for MPP and 666,3 (± 152,1 W) for PP. In response to this, velocity and power values for athletes during SJLoaded movement were obtained as 1,21 (±,10 m/sec) for MPV, 2,04 (± ,18 m/sec) for PV, 353,6 (± 83,2 W) for MPP and 666,3 (± 152,1 W) for PP. As a result, although there are many studies on physical or physiological characteristics of elite male footballers, the literature on the overall performance characteristics of women football players are limited. It is thought that the results obtained are important to fill this lack in the literature and will be the reference source for future research.